Resource-efficient methods for predicting and selecting heat-resistant alloys; Resource-Efficient Technologies; No 2 - Evdokimov V. B.; Artamonov A. A.; Plotnikov E. V.; Konstantinova N. A. (2019, 2019)
Title screen